ANALYSIS OF THE EFFECT OF INFLATION ON MUDHARABAH SAVING RESULTS AT MANDIRI SHARIA BANK 2015-2020 - Isthi Tresna Aristhantia; Jajang Saeful Hikmat; Diki Rahmat Awaludin (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Darussalam (IAID) Ciamis, Jawa Barat, INDONESIA, 2021)
This research was conducted to determine how the effect of inflation on revenue sharing from the Musyarakah financing contract, how the effect of operating costs on revenue sharing from the Musyarakah financing contract, and how the effect of inflation and operating costs together on revenue sharing from the financing contract. musharakah at PT. Bank Jabar Banten Syariah. This research is quantitative. The sample used in this study is in the form of monthly financial statements of PT. Bank Jabar Banten Syariah for the period 2017-2021 published on the official website of Bank Indonesia, the Financial Services Authority, and Bank Jabar Banten Syariah. The type of research data is secondary data. The results showed that partially inflation and operating costs had a positive and significant effect on revenue-sharing for the results of musyarakah financing. Taken together, inflation and operating costs have an impact on revenue-sharing from the Musyarakah financing contract, as evidenced by the probability-F statistic of 0.000038, which is much smaller than 0.05. Then the contribution of the variable inflation and operating costs to the income of musyarakah financing is 0.275489 or (27%). At the same time, the remaining 73% is explained by other variables that are not examined or are not included in this research model.